2015
DOI: 10.3126/ajms.v7i1.13044
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of burn injury with special reference to its prevention- A Nine-year retrospective study from a tertiary care hospital of West Bengal, India

Abstract: Burn injuries, generally have continued to attract the attention of researchers all over the world. Burn injuries rank among the most severe types of injuries suffered by the human body with an attendant high mortality and morbidity rate.1 Developing countries have a high incidence of burn injuries, creating a formidable public health problem. High population density, illiteracy, and poverty are the main demographic factors associated with a high risk of burn injury. The exact number of burn injury is diffi cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…Among 514 burn injury patients in the present study, majority were adults of 20-40 yrs (22.6%), similar to the study conducted by Chakraborty S et al [5] , Kuiri et al [6] , and Chatterjee S et al [7] in tertiary care hospitals of Kolkata, Bankura, Burdwan of West Bengal respectively and Goswami P et al [8] in Jamsedpur of Jharkhand. This age group is most frequently affected as they are mostly engaged in activities both indoor and outdoor.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Among 514 burn injury patients in the present study, majority were adults of 20-40 yrs (22.6%), similar to the study conducted by Chakraborty S et al [5] , Kuiri et al [6] , and Chatterjee S et al [7] in tertiary care hospitals of Kolkata, Bankura, Burdwan of West Bengal respectively and Goswami P et al [8] in Jamsedpur of Jharkhand. This age group is most frequently affected as they are mostly engaged in activities both indoor and outdoor.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to that, the study conducted by Bhansali CA et al in tertiary hospitals of Pune [11] , Gupta AK et al in Punjab [12] and Khasaba HA et al in Kuwait [9] showed it more among males. As like other studies, [5][6][7] majority of burn patients in the present study were from rural background, of primary education and of lower socioeconomic status. An epidemiological study in Indore by Moses S et al had also found the burn patients as mostly illiterates and of poor socioeconomic condition.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations